DOUBLE CONGELATION DE LA SEMENCE EQUINE (Effet de la concentration en glycérol et de la dilution finale sur la qualité spermatique) - SIDHOUM RECHIDI, Nadra (My University, 2019)
The objective of this study is to evaluate the effect of glycerol concentration, final sperm concentration, and treatment with cholesterol and α-tocopherol loaded cyclo-dextrins on equine sperm quality across two cryopreservation cycles. Two experiments were carried out. In experiment1, eighteen ejaculates harvested from six stallions were used. Each ejaculate was evaluated initially (CASA & CMF), then frozen in 1 commercial diluent (INRA FREEZE®, 2.5% glycerol) and four experimental diluents composed from (INRA96®) supplemented with 1%, 2%, 3% and 4% glycerol respectively thawed and evaluated again. A second freeze-thaw cycle was performed. The glycerol concentration giving the best result will be retained for the experiment2. In experiment 2, straws previously frozen in INRA-Freeze® were thawed and refrozen in three dilutions (1: 10, 1: 20, 1: 100) treated or not with cholesterol and α-tocopherol loaded cyclo-dextrins. An analysis (CASA and CMF) was performed after thawing. The concentration of 2.5% glycerol (INRA-Freeze ®) was optimal for a refreezing of equine spermatozoa. Centrifugation of the equine seed before refreezing (600xg, 10mn on a "Maxifreeze®" cushion) reduced the rate of cell loss to 12% associated with good acrosome viability. Treatment of the cholesterol and α-tocopherol loaded cyclo-dextrins(CLC + TLC) significantly improved the quality of equine spermatozoa (mobility, membrane and acrosomal integrity, and oxidative status) refreezed at low concentration of 1 million spermatozoa per milliliter, allowing production of 100 to 300 ICSI flakes from a conventional flake of AI.
Keywords: Stallion; semen; freezing; refreezing; CASA; flux Cytométrie